Multiconstrained aerodynamic design of business jet by CFD driven optimization tool - Peigin, Sergey; Epstein, Boris (Aerospace science and technology, 2008)
The problem of a multiconstrained aerodynamic design for business jet aircraft is considered. The objective of optimization is to minimize the total drag of an aircraft configuration subject to numerous geometrical and aerodynamical constraints. The optimization tool OPTIMAS is based on Genetic Algorithms search strategy and is driven by full Navier–Stokes computations. The results include a number of single- and multi-point optimizations for a generic business jet. For the considered design conditions, significant drag reduction in on- and off-design flight points has been achieved.